The Statistical Analysis of the Academic Achievement of Young People Living in the Child Protection System - Erdei, Ildikó; Kovács, Karolina Eszter (Central European Journal of Educational Research, 2020)
In recent years, there has been an increasing emphasis on placing children in foster care. Our main research aims to explore the connections between the future orientation of disadvantaged young people living in residential care homes and foster families. In our pilot-study, we made it measurable by a comparative analysis of their study results. The sample consists of children raised in the child protection specialist and aftercare system of the Greek Catholic Child Protection Centre of Debrecen and Nyírség. The comparative analysis included 57 children and young people living in residential care homes and 57 children and young adults living in foster care. The members of both groups were born between 1993 and 2003, so are 15-25-year-olds. The comparative analysis was made on the basis of the available documents and study statistics between June 2019 and November 2019, to measure and compare the academic achievement of young people living in residential care homes and with foster parents. According to the statistical analysis, it was found that the academic achievement, based on year repetitions, show a more favourable picture of students living with foster parents. Depending on our results, a number of additional research questions arise.